Diagnostic Concordance in Tertiary (Dermatologists-to-Experts) Teledermoscopy: A Final Diagnosis-Based Study on 290 Cases - Anne Marchetti; Stephane Dalle; Delphine Maucort Boulch; Mona Amini-Adl; Sébastien Debarbieux; Nicolas Poulalhon; Marie Perier-Muzet; Alice Phan; Luc Thomas (Mattioli1885, 2020)
Background: Teledermoscopy (TDS) improves diagnostic accuracy and decreases the number of unnecessary consultations. Objectives: To determine the diagnostic concordance in tertiary (dermatologist-to-experts) TDS with histopathology/follow-up-based diagnosis. Methods: A descriptive retrospective cohort study including 290 requests. Results: Perfect diagnostic concordance was found in 202 (69.7%) cases and partial agreement in 29 (10%). Disagreement was found in 59 (20.3%) cases. Perfect concordance on the benign/malignant nature of the lesion was found in 227 (78.3%) cases and disagreement in 63 (21.7%). In onychology, diagnostic concordance was perfect in 43 (76.8%) cases, partial in 7 (12.5%), and there was disagreement in 6 (10.7%). Final concordance on the benign/malignant nature of the lesion was perfect in 48 (85.7%) and there was disagreement in 8 (14.3%) nail cases. For pediatric requests, diagnostic concordance was perfect in 29 (65.9%) cases, partial in 5 (11.4%), and there was disagreement in 10 (22.7%). Final concordance on the benign/malignant nature of the lesion was observed in 34 (77.3%) cases, disagreement in 10 (22.7%). Conclusions: This study confirms that tertiary TDS improves diagnostic accuracy of pigmented skin lesions. Moreover, it shows encouraging results in unusual conditions such as ungual and pediatric skin tumors. The main limitation was the retrospective nature and the "real-life" setting of our study that could have created a selection bias toward inclusion of the most difficult cases.